The Effectiveness of the Traditional Game “Gobak Sodor” in Improving Ball Dribbling Skills in Grade 4 Students of Bontokamase Public Elementary School - Ihsan, Andi; Usman, Arifuddin (SHOOTING: Journal of Sport, Health, and Education, 2024)
This study aims to test the hypothesis that the traditional game Gobak Sodor is effective in improving dribbling skills in grade 4 students of Bontokamase State Elementary School. This study involved 50 students who were randomly divided into two groups: the experimental group (n=25) and the control group (n=25). The experimental group was given dribbling training integrated with the Gobak Sodor game for 4 weeks, while the control group only followed conventional dribbling learning. Data were collected through dribbling skills tests before and after treatment. The results of data analysis using paired t-test showed a significant increase in the average post-test score of the experimental group (M = 87, SD = 6.1) compared to the pre-test (M = 72, SD = 5.4), with a t(22) value = 3.41, p < 0.01. In contrast, there was no significant difference in the control group. These findings indicate that the Gobak Sodor game can be an effective intervention to improve dribbling skills in students of Bontokamase State Elementary School.